Strategi Pengurus Pondok Pesantren Dalam Menegakkan Peraturan Disiplin Santri - Saifudin, (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2023)
This research aims to explore and analyze the strategies used by Islamic boarding school administrators in enforcing student discipline regulations. The type of research used is a qualitative descriptive case study method. Data collection techniques use interviews and observation. The data analysis technique uses method triangulation and data source triangulation. Several methods or techniques for developing discipline; Enforcing Regulations, Islamic boarding schools enforce regulations, the supervisors or Ustadz and Ustadzah give rules to students in regulating communication with people outside the boarding school, move students through bells for each activity, and supervise the activities of students and Islamic boarding school students, as well as providing time for memorization. The research results show several strategies that are consistently implemented by Islamic boarding school administrators to enforce student discipline regulations: preventive education, consistent application of rules, involvement of the Islamic boarding school community, character development, and adaptation to environmental changes.